Method for reducing grain size of thermal sensitive ceramic with negative temperature coefficient by using high-energy ball milling

By performing high-energy ball grinding treatment on the presintered nano-oxide powder, the problem of grain growth in the preparation of NTC thermosensitive ceramics is solved, and the grain size reduction and electrical performance improvement are achieved, the process is simplified and reduced. The cost.

CN119462079APending Publication Date: 2025-02-18XINJIANG TECH INST OF PHYSICS & CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411622759.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the preparation of negative temperature coefficient (NTC) thermosensitive ceramics, nanopowders are prone to grain growth during high-temperature solid phase reaction and sintering, resulting in a decrease in electrical performance and stability, high operation difficulty and increased cost.

Method used

The pre-sintered powder is crushed by high-energy ball milling technology, and the ball mill is crushed by anhydrous ethanol and deionized water as medium, and combined with vacuum suction filtration and re-drying treatment, reducing the particle size of the ceramic powder.

Benefits of technology

Effectively reduces the grain size of the negative temperature coefficient (NTC) thermosensitive ceramics, improves electrical performance and stability, simplifies process operations and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462079A_ABST
    Figure CN119462079A_ABST
Patent Text Reader

Abstract

The invention relates to a method for reducing the grain size of negative temperature coefficient thermal sensitive ceramic by using high-energy ball milling, which comprises the following steps: weighing nano oxide powder, taking absolute ethyl alcohol as a medium, mixing and dispersing by using a planet wheel ball mill, drying the mixed slurry, firstly manually grinding and dispersing the dried powder, and then grinding and dispersing by using a high-energy ball mill; the preparation method comprises the following steps: carrying out high-temperature pre-sintering, carrying out ball-milling crushing on the pre-sintered powder by using a high-energy ball mill by using deionized water as a medium, carrying out vacuum filtration on slurry, drying again, pressing the dried powder by using a mold to form a ceramic green body, and finally carrying out high-temperature sintering to form the negative temperature coefficient thermal sensitive ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic component manufacturing, and in particular relates to a method for reducing the grain size of negative temperature coefficient (NTC) thermistor ceramics by using high-energy ball milling. Background Art

[0002] Negative temperature coefficient (NTC) thermistor is a sensitive element whose resistance decreases exponentially with increasing temperature. It is mainly made of oxides of transition metal elements such as manganese, iron, and nickel as raw materials and is formed by high-temperature sintering. A small temperature fluctuation will cause a significant change in the ceramic resistance. The electrical signal of this change in the circuit is collected, and the temperature change at the mK level can be detected. Therefore, it is the most sensitive type of temperature sensor at present. Driven by application requirements such as high precision, fast response, and miniaturization, negative temperature coefficient (NTC) thermistors are developing in the direction of sheet-type and microcrystallization. According to the formation mechanism of negative temperature coefficient (NTC) thermistor ceramics, the powder properties have a significant impact on the electrical properties and stability of thermistor ceramics. At present, sol-gel, coprecipitation and other methods have been developed to obtain nano-primitive oxide powders with uniform composition. However, since semiconductor ceramics are usually formed by high-temperature solid-phase reaction of primitive oxides, nano-powders are prone to sintering and growth during high-temperature heating, thereby losing their nanostructures. At present, sintering process control or special ceramic forming processes such as hot pressing sintering are usually adopted, which are difficult to operate and also increase the manufacturing cost. Therefore, it is urgent to develop effective means to effectively suppress the influence of high-temperature sintering on the grain size, which is of great significance for the preparation of high-quality NTC thermistors.

[0003] The present invention aims at the problem of grain growth of nanopowders during high-temperature solid-phase reaction and sintering in the preparation process of negative temperature coefficient (NTC) thermistor ceramics, and provides a convenient and effective control measure. The ceramic powder particle size is reduced by high-energy ball milling of the pre-sintered powder, thereby reducing the grain size of the negative temperature coefficient (NTC) thermistor ceramics. Summary of the invention

[0004] The present invention aims to provide a method for reducing the grain size of negative temperature coefficient thermistor ceramics by high-energy ball milling. The method adopts nano oxide powder, uses anhydrous ethanol as a medium, uses a ball mill for mixing and dispersion, dries the mixed slurry, grinds and disperses the dried powder manually, and then pre-sinters it at high temperature. The pre-sintered powder is milled and crushed again by a high-energy ball mill using deionized water as a medium, and is dried again after vacuum filtration. The dried powder is pressed by a mold to form a ceramic green body, and finally sintered at high temperature to form a negative temperature coefficient thermistor ceramic.

[0005] The method of reducing the grain size of negative temperature coefficient thermistor ceramics by high-energy ball milling described in the present invention is carried out according to the following steps:

[0006] a. Molar ratio of Mn:Ni:CoO 4 =1.25:0.75:1 weigh raw materials of nano manganese oxide, nano nickel oxide, and nano cobalt oxide powders, mix them with anhydrous ethanol as the medium, use a ball mill to mix, add zirconium oxide balls, the ball-to-material ratio is 2.5-10:1, the rotation speed is 300-2000rpm, mix for 8-12h, dry the mixed slurry at a temperature of 60-80°C for 24-48h, and then manually grind and disperse it with a mortar for 2h to obtain a mixture;

[0007] b. Pre-sintering of powder: placing the mixture obtained in step a into an alumina crucible, placing it in a resistance furnace, heating it to 850°C at a rate of 3°C / min, and keeping it at that temperature for 2h to pre-sinter the powder;

[0008] c. Ball milling: The powder pre-sintered in step b was milled in a high-energy ball mill with deionized water as the medium, using zirconium oxide grinding balls, a ball-to-material ratio of 10:1, and a rotation speed of 2000-3200 rpm for 8 hours. The slurry after ball milling was vacuum filtered using a microporous filter membrane with a pore size of 0.22 μm, and then dried at 80°C for 48 hours to remove moisture. The obtained powder was then manually ground and dispersed in a mortar for 2 hours;

[0009] d. Tablet forming: The powder dispersed in step c is loaded into a tableting mold with a mold diameter of 10 mm, and pre-pressed by a hydraulic press at a pressure of 20 MPa for 60 seconds, and then pressed by a cold isostatic press at a pressure of 350 MPa for 60 seconds to obtain a ceramic green sheet;

[0010] e. High-temperature sintering: Place the ceramic sheet green body of step d in a resistance furnace for high-temperature sintering at a sintering temperature of 1200° C., a heating rate of 3° C. / min, and a holding time of 2 h to obtain a sensitive body ceramic. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 A preparation route map for the negative temperature coefficient (NTC) thermistor ceramics of the present invention;

[0012] Figure 2 The particle size distribution diagram of the powder after pre-sintering and secondary ball milling in each embodiment of the present invention;

[0013] Figure 3 (a) The grain morphology of the NTC thermistor ceramic prepared by the process of Example 2; (b) The grain morphology of the NTC thermistor ceramic prepared by the process of Example 3. DETAILED DESCRIPTION

[0014] Example 1

[0015] a. Molar ratio of Mn:Ni:CoO 4 =1.25:0.75:1 Weigh nano manganese oxide, nano nickel oxide, and nano cobalt oxide powders with a particle size of 50 nm, use anhydrous ethanol as a medium, use a planetary wheel ball mill to mix, add zirconium oxide balls, the ball-to-material ratio is 2.5:1, the rotation speed is 300 rpm, mix for 12 hours, dry the mixed slurry at a temperature of 60°C for 24 hours, and then manually grind and disperse it with a mortar for 2 hours to obtain a mixture;

[0016] b. Pre-sintering the powder: placing the mixture obtained in step a in an alumina crucible, heating to 850° C. at 3° C. / min, and keeping the temperature for 2 h to pre-sinter the powder;

[0017] c. Ball milling: The powder pre-sintered in step b was milled in a high-energy ball mill with deionized water as the medium, using zirconium oxide grinding balls, a ball-to-material ratio of 10:1, and a rotation speed of 2000 rpm for 8 hours. The slurry after ball milling was vacuum filtered using a microporous filter membrane with a pore size of 0.22 μm. After filtration, it was dried at 80°C for 48 hours to remove moisture, and the obtained powder was manually ground and dispersed in a mortar for 2 hours;

[0018] d. Tablet forming: The powder dispersed in step c is loaded into a tableting mold with a mold diameter of 10 mm, and pre-pressed by a hydraulic press at a pressure of 20 MPa for 60 seconds, and then pressed by a cold isostatic press at a pressure of 350 MPa for 60 seconds to obtain a ceramic green sheet;

[0019] f. High-temperature sintering: Place the ceramic green body in a resistance furnace for high-temperature sintering at a sintering temperature of 1200°C, a heating rate of 3°C / min, and a holding time of 2h to obtain a sensitive body ceramic.

[0020] The particle size distribution of the powder obtained after pre-sintering and high-energy ball milling is as follows: Figure 2 As shown, the original powder particle size is 50nm, and the powder particle size after planetary wheel ball milling and pre-sintering is D 50 =955.4nm, D 90 =1106.4nm; after high-energy ball milling, the particle size of the powder is D 50 =50.7nm, D 90 =78.8nm.

[0021] Example 2

[0022] a. Molar ratio of Mn:Ni:CoO 4=1.25:0.75:1 Weigh nano manganese oxide, nano nickel oxide, and nano cobalt oxide powders with a particle size of 50 nm, use deionized water as a medium, use a planetary wheel ball mill to mix, add zirconium oxide balls, the ball-to-material ratio is 10:1, the rotation speed is 2000rpm, mix for 12 hours, and dry the mixed slurry at a temperature of 80°C for 48 hours. After drying, grind and disperse it manually with a mortar for 2 hours to obtain a mixture;

[0023] b. Pre-sintering of powder: placing the mixture obtained in step a into an alumina crucible, placing it in a resistance furnace, heating it to 850°C at 3°C / min, and keeping it at that temperature for 2h to pre-sinter the powder;

[0024] c. Ball milling: The pre-sintered powder was milled in a high-energy ball mill with deionized water as the medium and zirconium oxide grinding balls at a ball-to-material ratio of 10:1. The speed was 2000 rpm and the ball milling time was 8 hours. The slurry after ball milling was vacuum filtered with a microporous filter membrane with a pore size of 0.22 μm. After filtration, it was dried at 80°C for 48 hours to remove moisture. The obtained powder was then manually ground and dispersed in an agate mortar for 2 hours.

[0025] d. Tablet forming: The powder dispersed in step c is loaded into a tableting mold with a mold diameter of 10 mm, and pre-pressed by a hydraulic press at a pressure of 20 MPa for 60 seconds, and then pressed by a cold isostatic press at a pressure of 350 MPa for 60 seconds to obtain a ceramic green sheet;

[0026] f. High-temperature sintering: placing the ceramic green body obtained in step d in a resistance furnace for high-temperature sintering at a sintering temperature of 1200, a heating rate of 3, and a holding time of 2h to obtain a sensitive body ceramic;

[0027] The particle size distribution of the powder obtained after pre-sintering and high-energy ball milling is as follows: Figure 2 As shown, the original powder particle size is 50nm, and the powder particle size after high-energy ball milling and pre-sintering is D 50 =955.4nm, D 90 =1281.3nm; after high-energy ball milling, the particle size of the powder is D 50 =78.8nm, D 90 =91.28nm. The morphology of the thermal ceramic grains formed after the powder is pressed and sintered is as follows Figure 3 a.

[0028] Example 3

[0029] Comparative Example 1

[0030] a. Molar ratio of Mn:Ni:CoO 4=1.25:0.75:1 Weigh nano manganese oxide, nano nickel oxide, and nano cobalt oxide powders with a particle size of 50 nm, use anhydrous ethanol as a medium, use a planetary wheel ball mill to mix, add zirconium oxide balls, the ball-to-material ratio is 2.5:1, the speed is 300 rpm, mix for 12 hours, dry the mixed slurry at a temperature of 60°C for 24 hours, and then manually grind and disperse it with a mortar for 2 hours;

[0031] b. Pre-sintering the powder: placing the mixture obtained in step a in an alumina crucible, heating to 850° C. at 3° C. / min, and keeping the temperature for 2 h; performing a pre-sintering treatment on the powder;

[0032] c. Ball milling: The pre-sintered powder was milled with anhydrous ethanol as the medium using a planetary wheel ball mill, with zirconium oxide balls added, a ball-to-material ratio of 2.5:1, a rotation speed of 400 rpm, and a ball milling time of 24 h. The slurry after ball milling was vacuum filtered with a microporous filter membrane having a pore size of 0.22 μm. After filtration, it was dried at 60°C for 24 h. The obtained powder was then manually ground and dispersed in an agate mortar for 2 h.

[0033] d. Tablet forming: The powder dispersed in step c is loaded into a tableting mold with a mold diameter of 10 mm, and pre-pressed by a hydraulic press at a pressure of 20 MPa for 60 seconds, and then pressed by a cold isostatic press at a pressure of 350 MPa for 60 seconds to obtain a ceramic green sheet;

[0034] f. High-temperature sintering: Place the ceramic sheet green body obtained in step d in a resistance furnace for high-temperature sintering at a sintering temperature of 1200° C., a heating rate of 3° C. / min, and a holding time of 2 h to obtain a sensitive body ceramic.

[0035] The obtained powder particle size distribution after pre-sintering and planetary wheel ball milling is as follows: Figure 2 As shown, the original powder particle size is 50nm, and the powder particle size after planetary wheel ball milling and pre-sintering is D 50 =955.4nm,D 90 =1106.4nm; after being crushed by planetary wheel ball mill, the particle size of the powder is D 50 =1106.4nm, D 90 =1483.8nm. The morphology of the thermal ceramic grains formed after the powder is pressed and sintered is as follows Figure 3 b.

[0036] Example 4

[0037] Comparative Example 2

[0038] a. According to the molar ratio of Mn:Ni:CoO 4=1.25:0.75:1 Weigh nano manganese oxide, nano nickel oxide, and nano cobalt oxide powders with a particle size of 50 nm, use deionized water as the medium, use a high-energy ball mill to mix, use zirconium oxide grinding balls, a ball-to-material ratio of 10:1, a rotation speed of 2000 rpm, mix for 8 hours, dry the mixed slurry at a temperature of 80°C for 48 hours, and then manually grind and disperse it with a mortar for 2 hours;

[0039] b. Pre-sintering the powder: placing the mixture obtained in step a in an alumina crucible, heating to 850° C. at 3° C. / min, and keeping the temperature for 2 h; performing a pre-sintering treatment on the powder;

[0040] c. Ball milling: The pre-sintered powder obtained in step b was ball milled with anhydrous ethanol as the medium using a planetary wheel ball mill, with zirconium oxide balls added, a ball-to-material ratio of 2.5:1, a rotation speed of 400 rpm, and a ball milling time of 24 h. The slurry after ball milling was vacuum filtered with a microporous filter membrane having a pore size of 0.22 μm. After filtration, it was dried at a temperature of 60°C for 24 h, and the obtained powder was manually ground and dispersed in an agate mortar for 2 h.

[0041] d. Tablet forming: The powder dispersed in step c is loaded into a tableting mold with a mold diameter of 10 mm, and pre-pressed by a hydraulic press at a pressure of 20 MPa for 60 seconds, and then pressed by a cold isostatic press at a pressure of 350 MPa for 60 seconds to obtain a ceramic green sheet;

[0042] f. High-temperature sintering: Place the ceramic sheet green body obtained in step d in a resistance furnace for high-temperature sintering at a sintering temperature of 1200° C., a heating rate of 3° C. / min, and a holding time of 2 h to obtain a sensitive body ceramic.

[0043] The obtained powder particle size distribution after pre-sintering and planetary wheel ball milling is as follows: Figure 2 As shown, the original powder particle size is 50nm, and the powder particle size after high-energy ball milling and pre-sintering is D 50 =955.4nm, D 90 =1281.3nm; after being crushed by planetary wheel ball mill, the particle size of the powder is D 50 =825nm, D 90 =1106.4nm.

Claims

1. A method for reducing the grain size of negative temperature coefficient thermistor ceramics by high energy ball milling, characterized in that: Follow these steps: a. Weigh raw materials of nano manganese oxide, nano nickel oxide and nano cobalt oxide powders in a molar ratio of Mn: Ni: CoO4 = 1.25:0.75:1, mix them in a ball mill with anhydrous ethanol as the medium, add zirconium oxide balls, the ball-to-material ratio is 2.5-10:1, the rotation speed is 300-2000rpm, mix for 8-12 hours, dry the mixed slurry at a temperature of 60-80°C for 24-48 hours, and then grind and disperse it manually in a mortar for 2 hours to obtain a mixture; b. Pre-sintering of powder: placing the mixture obtained in step a into an alumina crucible, placing it in a resistance furnace, heating it to 850° C. at a rate of 3° C. / min, and keeping it at that temperature for 2 h to pre-sinter the powder; c. Ball milling: The powder pre-sintered in step b is milled in a high-energy ball mill with deionized water as the medium, using zirconium oxide grinding balls, a ball-to-material ratio of 10:1, and a rotation speed of 2000-3200 rpm for 8 hours. The slurry after ball milling is vacuum filtered using a microporous filter membrane with a pore size of 0.22 mm. After filtration, it is dried at 80°C for 48 hours to remove moisture, and the obtained powder is manually ground and dispersed in a mortar for 2 hours; d. Tablet molding: The powder dispersed in step c is loaded into a tableting mold with a mold diameter of 10 mm, and pre-pressed by a hydraulic press at a pressure of 20 MPa for 60 seconds, and then pressed by a cold isostatic press at a pressure of 350 MPa for 60 seconds to obtain a ceramic green sheet; e. High-temperature sintering: Place the ceramic sheet green body of step d in a resistance furnace for high-temperature sintering at a sintering temperature of 1200° C., a heating rate of 3° C. / min, and a holding time of 2 h to obtain a sensitive body ceramic.